2019
DOI: 10.1242/dev.175919
|View full text |Cite
|
Sign up to set email alerts
|

Root gravity response module guides differential growth determining both root bending and apical hook formation

Abstract: The apical hook is a transiently formed structure that plays a protective role when the germinating seedling penetrates through the soil towards the surface. Crucial for proper bending is the local auxin maxima, which defines the concave (inner) side of the hook curvature. As no sign of asymmetric auxin distribution has been reported in embryonic hypocotyls prior to hook formation, the question of how auxin asymmetry is established in the early phases of seedling germination remains largely unanswered. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 64 publications
4
46
0
Order By: Relevance
“…The cell wall status affects apical hook bending by transcriptional regulation of PINs and AUX1 through ARF2 (Aryal et al, 2020;Sampathkumar and Eng, 2020). Recently, it was shown that auxin gradient formed at the root tip by PIN2 is required for root growth in response to gravity (Zhu and Gallem, 2019). The root auxin gradient gradually extends toward hypocotyl and might trigger the hypocotyl bending resulting in hook formation.…”
Section: Hormonal Regulation Of Plant Development In Dark Apical Hookmentioning
confidence: 99%
“…The cell wall status affects apical hook bending by transcriptional regulation of PINs and AUX1 through ARF2 (Aryal et al, 2020;Sampathkumar and Eng, 2020). Recently, it was shown that auxin gradient formed at the root tip by PIN2 is required for root growth in response to gravity (Zhu and Gallem, 2019). The root auxin gradient gradually extends toward hypocotyl and might trigger the hypocotyl bending resulting in hook formation.…”
Section: Hormonal Regulation Of Plant Development In Dark Apical Hookmentioning
confidence: 99%
“…To test this hypothesis we quantified the growth increase over 6 hour period in radicle and hypocotyl of young seedling using confocal imaging (Fig. 5C) 82 . Indeed, root radicle grew significantly faster that adjacent hypocotyl( Fig.…”
Section: Anisotropic Growth Results From Differential Expansion At Thmentioning
confidence: 99%
“…Under these conditions the anisotropic growth of the root is self-organizing, later setting the polarity axis. (C) Screenshots from time-lapse imaging of growing radicle with PIP-GFP plasma membrane marker82 for a total time of 6 hours. (D) Percentage of growth increase per hour for adjacent organs radicle (root) and hypocotyl quantified from the time-lapse confocal imaging of three independent plants (n=3) .…”
mentioning
confidence: 99%
“…Although formation of the apical hook and its light‐regulated opening is known to be tightly regulated by several hormones (Wang & Guo, 2019), how ABA influences this process at the molecular level remains less understood. Indeed, the balance between ABA and gibberellic acid plays an important role in apical hook formation (Zhu et al ., 2019). HOOKLESS1 (HLS1), a central regulator of apical hook development, is induced by ABA and promotes ABA responses by directly activating ABI5 transcription, and indicates its position as an integration point for ABA signalling and hook development (Liao et al ., 2016).…”
Section: Aba Puts a Brake On Light‐induced Greening Of Seedlingsmentioning
confidence: 99%